Endoplasmic reticulum stress-induced autophagy determines the susceptibility of melanoma cells to dabrafenib - Ji C; Zhang ZP; Chen LH; Zhou KL; Li DJ; Wang P; Huang SY; Gong T; Cheng B (Dove Medical Press, 2016)
Chao Ji,1,2 Ziping Zhang,1,2 Lihong Chen,1,2 Kunli Zhou,1,2 Dongjun Li,1,2 Ping Wang,1,2 Shuying Huang,1,2 Ting Gong,2 Bo Cheng1,2 1Department of Dermatology, the 1st Affiliated Hospital of Fujian Medical University, 2Fujian Institute of Dermatology and Venereology, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China Abstract: Melanoma is one of the deadliest skin cancers and accounts for most skin-related deaths due to strong resistance to chemotherapy drugs. In the present study, we investigated the mechanisms of dabrafenib-induced drug resistance in human melanoma cell lines A375 and MEL624. Our studies support that both endoplasmic reticulum (ER) stress and autophagy were induced in the melanoma cells after the treatment with dabrafenib. In addition, ER stress-induced autophagy protects melanoma cells from the toxicity of dabrafenib. Moreover, inhibition of both ER stress and autophagy promote the sensitivity of melanoma cells to dabrafenib. Taken together, the data suggest that ER stress-induced autophagy determines the sensitivity of melanoma cells to dabrafenib. These results provide us with promising evidence that the inhibition of autophagy and ER stress could serve a therapeutic effect for the conventional dabrafenib chemotherapy. Keywords: melanoma, dabrafenib, ER stress, autophagy, apoptosis